(untitled) (REVISTA NODO, 2024)
There have been many researchers who have had the pleasure of participating in the projects and initiatives developed by Anna Maria Guasch from the University of Barcelona, ​​of which she is today an emeritus professor. On a personal note, I can say that I have had the privilege of accompanying her closely in the construction of this critical debate around the global turn in art studies and of having actively participated in the expansion of the geo-epistemological horizons of the program in Theory, History and Criticism of the Arts at the University of Barcelona. Two decades later, it is easy to see that the dialogue with Anna Maria has been nutritious and plural.